Effects of MgO Particle Loading on Gas Permeation Properties of Epoxidized Natural Rubber (ENR) / polyvinyl chloride (PVC) Membrane - Farhan Mohd Nor,; Rizafizah Othaman, (Universiti Kebangsaan Malaysia, 2015)
A composite membrane was prepared by mixing epoxidized natural rubber (ENR) and polyvinyl chloride (PVC). An inorganic filler, MgO, was introduced into the polymer matrix by certain percentages to form a mixed matrix membrane (MMM). The resulting membranes were characterized using FTIR, TGA, SEM and gas permeability test. FTIR results showed the incorporation of MgO inside the membrane matrix with the appearance of an absorption peak at 3700 cm-1 which represents the formation of Mg(OH)2. Thermogram from TGA analysis showed two degradation stages at 250-350°C and 370-500°C, which correspond to the decomposition of PVC and ENR and the residue of fillers at 600°C. SEM images of the membranes showed that pores were developed as fillers were introduced to the membrane. The size of the pores also increased with the increase of filler percentage. As for gas permeation test, the permeability values of CO2 and N2 for ENR/PVC membrane were the lowest. The permeability values increased with the addition of MgO to the membrane. The permeability of CO2 was also the highest for all membranes.